Nurse-based educational interventions in patients with peritoneal dialysis: A systematic review and meta-analysis - Tanawin Nopsopon; Piyawat Kantagowit; Chitsanucha Chumsri; Piyaporn Towannang; Apinya Wechpradit; Nipa Aiyasanon; Ruchdaporn Phaichan; Talerngsak Kanjanabuch; Krit Pongpirul (Elsevier, 2022)
Background: Peritoneal dialysis (PD) is a major renal replacement therapy modality for patients with end-stage kidney disease (ESKD) worldwide. As poor self-care of PD patients could lead to serious complications, including peritonitis, exit-site infection, technique failure, and death; several nurse-based educational interventions have been introduced. However, these interventions varied and have been supported by small-scale studies so the effectiveness of nurse-based educational interventions on clinical outcomes of PD patients has been inconclusive. Objectives: To evaluate the effectiveness of nurse-based education interventions in PD patients. Design: A systematic review and meta-analysis of Randomized Controlled Trials (RCTs). Methods: We performed a systematic search using PubMed, Embase, and CENTRAL up to December 31, 2021. Selection criteria included Randomized Controlled Trials (RCTs) relevant to nurse-based education interventions in ESKD patients with PD in the English language. The meta-analyses were conducted using a random-effects model to evaluate the summary outcomes of peritonitis, PD-related infection, mortality, transfer to hemodialysis, and quality of life (QoL). Results: From 9,816 potential studies, 71 theme-related abstracts were selected for further full-text articles screening against eligibility criteria. As a result, eleven studies (1,506 PD patients in seven countries) were included in our systematic review. Of eleven studies, eight studies (1,363 PD patients in five countries) were included in the meta-analysis. Sleep QoL in the intervention group was statistically significantly higher than control (mean difference = 12.76, 95% confidence intervals 5.26-20.27). There was no difference between intervention and control groups on peritonitis, PD-related infection, HD transfer, and overall QoL. Conclusions: Nurse-based educational interventions could help reduce some PD complications, of which only the sleep QoL showed statistically significant improvement. High-quality evidence on the nurse-based educational interventions was limited and more RCTs are needed to provide more robust outcomes. Tweetable abstract: Nurse-based educational interventions showed promising sleep quality improvement and potential peritonitis risk reduction among PD patients.